BRANDING OF LIBRARY IN IMPROVING PUBLIC READING INTEREST IN LABUHAN BATU SELATAN REGENCY - Putoro, Adimas Sutan; Harahap, Nursapia (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study discusses library branding strategies in increasing public interest in reading in South Labuhan Batu Regency, a developing area in North Sumatra. The phenomenon of low reading interest in Indonesia demands a more contextual and adaptive literacy strategy for the digital era. With a qualitative approach and descriptive design, this study is based on a constructivist paradigm that places reality as a result of social construction. Primary data were collected through in-depth interviews with the head of the library, librarians, and service users, as well as participatory observation and documentation. Meanwhile, secondary data were obtained from journals, books, and scientific articles. The data analysis technique used the Miles, Huberman, and Saldana model which includes reduction, presentation, and drawing conclusions, and was complemented by a validity test through source triangulation. The results of the study showed that the branding strategy was carried out comprehensively through social media, service innovations such as mini cinemas, and collaboration with schools and literacy communities. Branding has proven effective in increasing the number of visits, new memberships, and public interaction through digital channels. However, significant challenges were found in the form of limited digital infrastructure, low technological literacy in rural areas, and conservative perceptions of the function of libraries. The branding strategy implemented is able to build the library's identity as an inclusive and modern literacy institution, as analyzed in the perspective of brand identity theory. In conclusion, branding is not only a promotional instrument, but also a transformational strategy in shaping the image.